2021
DOI: 10.1007/s00277-021-04534-8
|View full text |Cite
|
Sign up to set email alerts
|

Real-world comparative effectiveness of triplets containing bortezomib (B), carfilzomib (C), daratumumab (D), or ixazomib (I) in relapsed/refractory multiple myeloma (RRMM) in the US

Abstract: Multiple available combinations of proteasome inhibitors, immunomodulators (IMIDs), and monoclonal antibodies are shifting the relapsed/refractory multiple myeloma (RRMM) treatment landscape. Lack of head-to-head trials of triplet regimens highlights the need for real-world (RW) evidence. We conducted an RW comparative effectiveness analysis of bortezomib (V), carfilzomib (K), ixazomib (I), and daratumumab (D) combined with either lenalidomide or pomalidomide plus dexamethasone (Rd or Pd) in RRMM. A retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 29 publications
2
41
0
Order By: Relevance
“…While clinical trials demonstrate impressive benefit of darabased therapies, possible discordance with real-world practice might exist, as many patients in the real world are known to be ineligible for clinical trials. 22,23 A few small real-world multicentre studies specifically focusing on dara have been published, confirming the promising activity noted in clinical trials [23][24][25][26][27] [28][29][30][31] There remains a paucity of studies evaluating the outcomes of dara-containing regimens in larger realworld cohorts. Our study aimed to evaluate the impact of these regimens and to benchmark outcomes that may identify gaps that can be targeted for future optimization.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…While clinical trials demonstrate impressive benefit of darabased therapies, possible discordance with real-world practice might exist, as many patients in the real world are known to be ineligible for clinical trials. 22,23 A few small real-world multicentre studies specifically focusing on dara have been published, confirming the promising activity noted in clinical trials [23][24][25][26][27] [28][29][30][31] There remains a paucity of studies evaluating the outcomes of dara-containing regimens in larger realworld cohorts. Our study aimed to evaluate the impact of these regimens and to benchmark outcomes that may identify gaps that can be targeted for future optimization.…”
mentioning
confidence: 77%
“…Comparing our results to other real‐world studies in this field is challenging given the paucity of data among real‐world patients utilizing dara‐containing regimens. Other such studies have recently been published, almost exclusively in the relapse setting, and the number of patients included were most often less than 100 23‐27 (Atrash et al, 2021; Harvanová et al, 2021; Maouche et al, 2021; Szabo et al, 2021). Additionally, many of these studies focused on patients receiving dara monotherapy 24‐27 (Atrash et al, 2021; Maouche et al, 2021; Szabo et al, 2021) and demonstrated results similar to those for our DaraD/P cohort.…”
Section: Discussionmentioning
confidence: 99%
“…reported data on the use of several pomalidomide-based triplets in the US, even though some of them have not yet been authorized in Europe (e.g., carfilzomib-pomalidomide-dexamethasone [KPd] and ixazomib-pomalidomide-dexamethasone [IPd]). Overall, 348 patients received a pomalidomide-based triplet, in most cases as a third or subsequent line of treatment, with favorable TTNT with PVd vs. IPd and KPd ( 52 ). In the phase III OPTIMISMM trial, PVd showed similar outcomes, with a median PFS of 11 months in a population of patients with a median of 2 prior lines of therapy ( 48 ).…”
Section: Immunomodulatory Drugsmentioning
confidence: 99%
“…analyzed data from patients with ≥2 prior lines of treatment treated with several combinations of novel agents with the backbones Rd or Pd. In this study, a subgroup of patients was treated with the KRd triplet (n=218), showing an overall dismal prognosis, as compared with that in patients treated with daratumumab-Rd and other Rd-containing combinations (median DOT: 7 months) ( 52 ). The DOT was shorter than that in the ASPIRE trial (16.5 months).…”
Section: Proteasome Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation